Electroencephalographic Seizures In Emergency Department Patients Following Treatment For Convulsive Status Epilepticus - Zehtabchi, Shahriar (J Clin Neurophysiol, 2022)
INTRODUCTION: It is unknown how often and how early electroencephalography (EEG) is obtained in patients presenting with status epilepticus. The Established Status Epilepticus Treatment Trial (ESETT) enrolled patients with benzodiazepine-refractory seizures and randomized participants to fosphenytoin, levetiracetam, or valproate. We determined use of early EEG, including frequency of electrographic seizures, in ESETT participants. METHODS: Secondary analysis of 475 enrollments at 58 hospitals to determine the frequency of EEG performed within 24 hours of enrollment. We recorded the EEG type, the prevalence of electrographic seizures, and characteristics associated with obtaining early EEG. Chi-square and Wilcoxon rank-sum tests were calculated as appropriate for univariate and bivariate comparisons. Odds ratios (OR) are reported with 95% confidence intervals. RESULTS: A total of 278/475 patients (58%) in the ESETT cohort underwent EEG within 24 hours (median time to EEG: 5 hours [IQR 3–10]). Electrographic seizure prevalence was 14% (95%CI, 10–19%; 39/278) in entire cohort and 13% (95%CI, 7–21%) in the subgroup of patients meeting the primary outcome of the ESETT trial (clinical treatment success within 60 minutes of randomization). Among subjects diagnosed with electrographic seizures (39), 15 (38%, 95%CI, 25–54%) had no clinical correlate on the video EEG recording. CONCLUSION: Electrographic seizures may occur in patients who stop seizing clinically after treatment of convulsive status epilepticus. Clinical correlates might not be present during electrographic seizures. These findings support early initiation of EEG recordings in patients suffering from convulsive status epilepticus, including those with clinical evidence of treatment success.